Perancangan model bisnis cinderamata sebagai implementasi social entrepreneurship - Rifa'i Rifa'i; Muhammad Ridwan Andi Purnomo; Taufiq Immawan (Teknoin, 2017)
Strategic location, near by national economic center, exposes Banten with positive vibe for its economic growth. Nevertheless, according to existing data, on the 3rd quarter in 2015, tourism sector only reached 2,6% of market share. Thus, it hasn’t been existed as featured sectors. It appears due to several reasons, one of them is supporting component for this cultural creative industry that still under-developed. One of the local creative industries that has purpose to promote the uniqueness value of Banten culture through local souvenirs is Ora Bae (OB). This business is built based on social entrepreneurship. OB was established in 2013. However, the designated business model, apparently do not consistent with the income.Referring to above problem, therefore this research is conducted to identify and evaluate the existing business model as well as to design appropriate one. This research is carried out by implementing direct observation in Ora Bae Souvenir Shop and several Small and Middle Enterprises (SMEs) under it. The interview is performed by using SWOT concept that integrated with Business Model Canvas (BMC).Later, the results of observation and interview are used as the current business model formula that will be employed for SWOT analysis. Its results will be applied as basic for determining the business model alternative. Blue Ocean Strategy is employed to eliminate elements of business model that are insignificant and to create innovation in the latest business model. The improvement conceptsare conducted by enhancing the numberscostume’s designersto anticipate new customers’ segmentation, neglecting low price components on offered price proposition, improving the products’ distribution channel on places that potentially could maximize the available channelsby participatingin Banten events as advertising service. The improvements are also supported by resources in IT Support. In maintaining the relationship with customers, it is required additional services such as personal assistance and customer care. The innovation of this recent business model is expected to be the alternative for solution on problems that encountered by Ora Bae brand.